Corticobulbar projections from distinct motor cortical areas to the reticular formation in macaque monkeys. (2nd May 2017) - Fregosi, Michela; Contestabile, Alessandro; Hamadjida, Adjia; Rouiller, Eric M.
Abstract: Corticospinal and corticobulbar descending pathways act in parallel with brainstem systems, such as the reticulospinal tract, to ensure the control of voluntary movements via direct or indirect influences onto spinal motoneurons. The aim of this study was to investigate the corticobulbar projections from distinct motor cortical areas onto different nuclei of the reticular formation. Seven adult macaque monkeys were analysed for the location of corticobulbar axonal boutons, and one monkey for reticulospinal neurons' location. The anterograde tracer BDA was injected in the premotor cortex (PM), in the primary motor cortex (M1) or in the supplementary motor area (SMA), in 3, 3 and 1 monkeys respectively. BDA anterograde labelling of corticobulbar axons were analysed on brainstem histological sections and overlapped with adjacent Nissl‐stained sections for cytoarchitecture. One adult monkey was analysed for retrograde CB tracer injected in C5‐C8 hemispinal cord to visualise reticulospinal neurons. The corticobulbar axons formed bilateral terminal fields with boutons terminaux and en passant, which were quantified in various nuclei belonging to the Ponto‐Medullary Reticular Formation (PMRF). The corticobulbar projections from both PM and SMA tended to end mainly ipsilaterally in PMRF, but contralaterally when originating from M1. Furthermore, the corticobulbar projection was less dense when originating from M1 than from non‐primary motor areas (PM, SMA). The main nuclei of bouton terminals corresponded to the regions where reticulospinal neurons were located with CB retrograde tracing. In conclusion, the corticobulbar projection differs according to the motor cortical area of origin in density and laterality. Abstract : The corticobulbar (corticoreticular) projections to the ponto‐medullary reticular formation (PMRF) from premotor (PM) and supplementary motor (SMA) cortical areas are denser than that originating from primary motor cortical area (M1). Corticobulbar axon terminals in PMRF coming from M1 are predominantly contralateral, whereas PM and SMA project more densely ipsilaterally. When originating from PM and SMA, corticobulbar terminals are located more medially than when originating from M1.